Public Accountability: The Perceived Usefulness of School Annual Reports - Stuart Tooley; Jill Hooks (Australasian Accounting, Business and Finance Journal, 2010)
Annual reports are an important component of New Zealand schools’ public accountability. Through the annual report the governance body informs stakeholders about school aims, objectives, achievements, use of resources, and financial performance. This paper identifies the perceived usefulness of the school annual report to recipients and the extent to which it serves as an instrument of accountability and/or decision-usefulness. The study finds that the annual report is used for a variety of purposes, including: to determine if the school has conducted its activities effectively and achieved stated objectives and goals; to examine student achievements; to assess financial accountability and performance; and to make decisions about the school as a suitable environment for their child/children. Nevertheless, the study also finds that other forms of communication are more important sources of information about the school than the annual report which is seen to fall short of users’ required qualities of understandability, reliability and readability. It would appear imperative that policy makers review the functional role of the school annual report which is a costly document to prepare. Further, school managers need to engage in alternative means to communicate sufficient and meaningful information in the discharge of public accountability.
Keywords: Public accountability; School annual reporting; New Zealand